2014
DOI: 10.1186/1471-2458-14-567
|View full text |Cite
|
Sign up to set email alerts
|

Exploring obesogenic environments: the design and development of the migrant obesogenic perception of the environment questionnaire (MOPE-Q) using a sample of Iranian migrants in Australia

Abstract: BackgroundAlthough there are a number of studies examining the effect of migration on obesity, these studies tend to focus on the role of acculturation in this relationship. However, there are indications that the change in environment may also be an important factor. Indeed, there is a considerable lack of psychometric tools designed to assess the association between environment and migrant health behaviour. The current study aimed to assess the literature on the link between environment and health for migran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Evidence shows that obesogenic environments are found in disadvantaged areas with a high proportion of CALD communities. 25,31 As found elsewhere, 32,33 CALD parents in our study prioritised program accessibility barriers including lack of a driver's licence and car ownership, poor public transport facilities and long distances. We found that poor adjustment to the cold weather in Victoria and lack of indoor playparks for children were key barriers for CALD groups.…”
Section: Discussionsupporting
confidence: 59%
“…Evidence shows that obesogenic environments are found in disadvantaged areas with a high proportion of CALD communities. 25,31 As found elsewhere, 32,33 CALD parents in our study prioritised program accessibility barriers including lack of a driver's licence and car ownership, poor public transport facilities and long distances. We found that poor adjustment to the cold weather in Victoria and lack of indoor playparks for children were key barriers for CALD groups.…”
Section: Discussionsupporting
confidence: 59%
“…Finally, the Migrant Obesogenic Perception of the Environment questionnaire (MOPE-Q) [ 25 ] was used to gauge the experience of environmental determinants of obesity. The MOPE-Q was specifically developed for the measurement of the influence of environments on migrant obesity and has been demonstrated to be both valid and reliable in this context [ 25 ]. This questionnaire is a 17-item scale designed to measure the environmental determinants of obesity that migrants might experience in Australia.…”
Section: Methodsmentioning
confidence: 99%
“…Environments are defined as the sum of influences of surroundings, opportunities, or conditions of life [ 25 ]. Dissecting this further, Swinburn et al .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations